2010
DOI: 10.1099/mic.0.034579-0
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide radical induces sclerotial differentiation in filamentous phytopathogenic fungi: a superoxide dismutase mimetics study

Abstract: This study shows that the superoxide radical (O 2˙" ), a direct indicator of oxidative stress, is involved in the differentiation of the phytopathogenic filamentous fungi Rhizoctonia solani, Sclerotinia sclerotiorum, Sclerotium rolfsii and Sclerotinia minor, shown by using superoxide dismutase (SOD) mimetics to decrease their sclerotial differentiation. The production rate of O 2˙" and SOD levels in these fungi, as expected, were significantly lowered by the SOD mimetics, with concomitant decrease of the indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…We observed motifs for binding the regulators of oxygen metabolism, sexual development, and defense PR proteins in the nox1 promoter region. These data are in agreement with the role of Nox proteins as critical enzymes for sexual development (2,24,30) and sclerotial differentiation (39) in filamentous fungi, plant infection processes (10), and antimicrobial activity due to their involvement in ROS production (15,51).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We observed motifs for binding the regulators of oxygen metabolism, sexual development, and defense PR proteins in the nox1 promoter region. These data are in agreement with the role of Nox proteins as critical enzymes for sexual development (2,24,30) and sclerotial differentiation (39) in filamentous fungi, plant infection processes (10), and antimicrobial activity due to their involvement in ROS production (15,51).…”
Section: Discussionsupporting
confidence: 88%
“…It is well documented that ROS can induce sclerotial metamorphosis in R. solani (39), but this pathogen can also repress ROS formation through the production of the scavenger ascorbic acid in certain concentration gradients and proportions in response to oxidative stress caused by ROS during mycelial and sclerotial differentiation (13). On the other hand, B. cinerea seems to be better adapted to oxidative stress than other phytopathogens since it has been observed that ROS function generated by Nicotiana benthamiana has a positive role in expansion of disease lesions during B. cinerea-plant interaction (3).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies in sclerotiogenic fungi, high levels of H 2 O 2 inhibit SD because H 2 O 2 promotes intense cell proliferation throughout the whole mycelial colony. Such extensive cell proliferation surpasses the localized cell proliferation that is required for the generation of sclerotial initials (that are developed to mature sclerotia) (4,36,(46)(47)(48). Therefore, our data suggest that the increase in the SOD activity, combined with the decrease in CAT activity in the mutant strain compared to the control and the consequent increase in the concentration of H 2 O 2 , could contribute to the prevention of SD in the ⌬veA mutant strain.…”
Section: Grintzalis Et Almentioning
confidence: 71%
“…Enzyme activities were expressed per protein, the concentration of which was determined as previously described (28). The SOD specific activity was assayed as previously reported (36) and expressed as SOD units per mg of protein (using a standard curve made with pure bovine erythrocyte SOD). The CAT specific activity was measured with a Clark-type O 2 electrode (controlled by Oxygraph Plus software [Hansatech Instruments Co., England] provided by Hansatech) by monitoring the decomposition of H 2 O 2 to O 2 (in a 1-ml assay solution containing 0.3 mM H 2 O 2 in 10 m⌴ phosphate buffer [pH 7.0] with or without a 1 mM concentration of the CAT inhibitor ATR).…”
mentioning
confidence: 99%
“…Oxidative stress has been suggested to be involved in the differentiation of several fungi, including Aspergillus nidulans, N. crassa, Rhizoctonia solani, Sclerotinia sclerotiorum and Sclerotinia minor, and in Sclerotium rolfsii, sclerotial biogenesis in response to mycelial injury occurs as a result of oxidative stress (Aguirre, et al, 2005;Georgiou et al, 2006;Papapostolou & Georgiou, 2010).…”
Section: Mycelial Injurymentioning
confidence: 99%